Briefing: High-performance computing for city-scale modelling and simulations. Issue 4 (26th January 2018) - Soga, Kenichi; Casey, Gerard; Kumar, Krishna; Zhao, Bingyu
Abstract : Smarter cities and infrastructure are essential if the world is to respond effectively to the critical challenges it faces. As of 2008, and for the first time in human history, more than half of the world's population now live in cities. Yet cities increasingly need to be able to do more with less, to provide for the well-being of their citizens in a truly sustainable way. City-scale simulations are becoming a possibility with advancements in the computing hardware and software technologies. Recent advancements in distributed scaling using Apache Spark is exemplified through a case-study on simulating the traffic flow behaviour of London at per-hour time resolution. The case-study on the response of ground and structures in central Tokyo shows the advancements in multigrid techniques and Finite Element simulations. This paper discusses the advancements and challenges in high-performance computing (hardware, algorithms, software, and visualisation techniques) in achieving the possibility of real-time city-scale simulations.